The Impact of Implementing Good Aquaculture Practices (GAP) on Productivity of Shrimp Farmers in Bangil District, Pasuruan Regency, East Java: Good Aquaculture Practices and Productivity - Wijadmono, Erzhafira Nur Salsabila Putri; Andriatmoko, Novil Dedy; Satria, Awang Tri (Journal of Tropical Rural Development, 2025)
Background and purpose – East Java is one of the centers of shrimp production in Indonesia. However, productivity from 2021 to 2023 has decreased significantly by 62.5%. This decline occurred because there are still many farmers who apply cultivation practices that are not in accordance with SOPs. As a result, the mortality rate of shrimp increases which causes a decrease in productivity. This study aims to analyze the level of GAP practices of farmers, factors that influence farmers' decisions to apply GAP, and the impact of GAP implementation on productivity. Methodology – This research was conducted on shrimp farmers in Bangil District with using accidental sampling. The level of GAP practices of farmers was measured using descriptive statistics, then the factors influencing farmers' decisions were analyzed using probit regression, and the impact of GAP implementation on productivity was analyzed using Propensity Score Matching (PSM). Findings – The results showed that the level of GAP practices of farmers was still relatively low at 41.62%. Factors that influence the decision of farmers to adopt GAP are access to counseling, distance to the pond, education, cultivation experience, and off-farm work. high level of GAP implementation has a significant positive effect on increasing productivity. Implications – To improve the implementation of GAP, training, improved facilities, and support from the government or related institutions. Access to extension variables have a positive and significant effect on farmers' decisions to implement GAP practices, so that the government and extension workers can improve extension programs and training as well as equal distribution of information related to Good Aquaculture Practices (GAP) to farmers so that all farmers have access to extension.